Public opinion on alcohol policies in Sri Lanka - Chandraratne, Nadeeka K.; Negi, Nalin Singh; Siyambalapitiya, Hasini; De Seram, Sampath; Selladurai, Nidarshana; Pieris, Karieshini; Rothenstein-Henry, Rachel; Murukutla, Nandita (Frontiers in Public Health, 2024)
Background Alcohol imposes a significant burden on health, social and economic systems in Sri Lanka. In the present economic crisis taxes on alcohol provides necessary revenue increases. Yet, the perception of the public on alcohol policies in Sri Lanka is not well explored. Objectives This opinion survey was conducted with the aim to understand the public’s awareness on alcohol harm, alcohol industry influences, barriers and facilitators for implementing alcohol control policies in Sri Lanka, and the level of public support for alcohol policies, particularly taxes on alcohol products. Methods A street intercept survey among 997 participants (with a ratio of 2:1 for males and females) selected through a cluster sampling method responded to an interviewer administered questionnaire. Bivariate and multivariate analyses were conducted to determine associations and a p < 0.05 was considered significant. Results Among the respondents, 36.1% have consumed alcohol at least once in their lifetime and 29.1% have consumed alcohol during the past 12 months with a significant gender difference (females - 2.8%; males- 43.4%; p < 0.001). Significant proportions of both men (81.4%) and women (71.8%); p < 0.017 agreed that policy measures to reduce alcohol consumption would benefit the government including a significant proportion (73.8%, p < 0.008) of alcohol users. The vast majority −72.8%- agreed that increasing alcohol prices would help address the alcohol consumption problem in Sri Lanka. Moreover, only 30.8% of men and 44.3% of women agreed that the government’s alcohol laws are currently strong enough to protect people from alcohol harm. The regression analysis revealed that men are 2.43 times more in agreement with the statement that “policy measures aimed at reducing alcohol consumption can benefit the public” as compared to women. However, individuals aged 50–64 years are 40% less likely to agree with this statement as compared to 18–33 years. Conclusion The majority of the public, including people who consume alcohol, are supportive of improving alcohol related policies, including taxes, and acknowledge negative impact of alcohol consumption on the country. This presents a clear opportunity for Sri Lanka to strengthen and enforce the alcohol related policies to protect and improve public health.